Đơn giản biểu thức: B=(a/√ab+b)+(b/√ab- a)-(a+b/√ab) (a>0, b>0, a khác b)

Đơn giản biểu thức: B=(a/√ab+b)+(b/√ab- a)-(a+b/√ab) (a>0, b>0, a khác b)

0 bình luận về “Đơn giản biểu thức: B=(a/√ab+b)+(b/√ab- a)-(a+b/√ab) (a>0, b>0, a khác b)”

  1. Đáp án:

    $\begin{array}{l}
    Dkxd:a > 0;b > 0;a \ne b\\
    B = \dfrac{a}{{\sqrt {ab}  + b}} + \dfrac{b}{{\sqrt {ab}  – a}} – \dfrac{{a + b}}{{\sqrt {ab} }}\\
     = \dfrac{a}{{\sqrt b \left( {\sqrt a  + \sqrt b } \right)}} + \dfrac{b}{{\sqrt a \left( {\sqrt b  – \sqrt a } \right)}} – \dfrac{{a + b}}{{\sqrt {ab} }}\\
     = \dfrac{{a.\sqrt a \left( {\sqrt b  – \sqrt a } \right) + b.\sqrt b .\left( {\sqrt a  + \sqrt b } \right) – \left( {a + b} \right)\left( {b – a} \right)}}{{\sqrt {ab} \left( {b – a} \right)}}\\
     = \dfrac{{a\sqrt {ab}  – {a^2} + b\sqrt {ab}  + {b^2} – \left( {{b^2} – {a^2}} \right)}}{{\sqrt {ab} \left( {b – a} \right)}}\\
     = \dfrac{{a\sqrt {ab}  + b\sqrt {ab} }}{{\sqrt {ab} \left( {b – a} \right)}}\\
     = \dfrac{{\sqrt {ab} \left( {a + b} \right)}}{{\sqrt {ab} \left( {b – a} \right)}}\\
     = \dfrac{{a + b}}{{b – a}}
    \end{array}$

    Bình luận

Viết một bình luận